Network Security from the Perspective of the Internet of Things - Zhou, Ang (Journal of physics. Conference series, 2022)
Networking is one of the new technologies supported by our country’s national “125” strategic industry plan, mainly used in medicine, military industry, transportation and other fields. While enjoying the convenient business of the, people also pay more attention to the security of the Internet of Things information system. Therefore, this article mainly discusses security under the perspective of the IoT, and understands the relevant basic theoretical knowledge about the IoT and security on the basis of a large number of documents, and then conceives the security methods under the perspective of the IoT, and the designed method has been tested, and the test results show that the performance of the encryption algorithm in the network security scheme of this article is due to the traditional encryption algorithm. When the encrypted text is 15000 bytes, the encryption time is 40s.